LAND TENURE SECURITY PERMUKIMAN SEMPADAN SUNGAI MENTAYA, KABUPATEN KOTAWARINGIN TIMUR, KALIMANTAN TENGAH - Nur Kumala Ratih; Landung Esariti (Teknik PWK (Perencanaan Wilayah Kota), 2018)
The Mentaya riverine settlement located in Sampit is a historic settlement that becomes the city's growth embryo. The current development shows significant threat over its exploitation on physical construction on river surrounding. Therefore, this study aims to identify the form of land ownership protection of the Mentaya riverine settlement. The research located in 3 corridors, namely Corridor I Baamang, Corridor II Ketapang and Corridor III Mentaya Seberang. By using the quantitative method of observation, in depth interview and super impose maps this research obtains several findings.The first finding identifies local wisdom in terms of social aspects reflected in the social ties of society and environmental aspects reflected in the elements and patterns of settlements. The most prominent elements of settlement and the local wisdom of the Mentaya riverine settlement are the elements of social capital and dwelling design. The second findings related to land tenure security are in the form of the policy of the Regional Government of Kotawaringin Timur Regency as outlined in the Mater Plan of Kotawaringin Timur Regency (Local Regulation No.5 Year 2015). It is discussed in more detail in the draft of Detail Master Plan of Sampit City (RDTR) Year 2016 with the assertion of zoning confirmation and detail arrangement of Mentaya River as a residential area that has a traditional and cultural value. This later is legalized by the issuance of Land Certificate (SKT) by the Kelurahan Office.